A DNA barcoding approach to identify plant species in multiflower honey. (1st March 2015) - Bruni, I.; Galimberti, A.; Caridi, L.; Scaccabarozzi, D.; De Mattia, F.; Casiraghi, M.; Labra, M.
Highlights: Honey is a food product potentially constituted by different plant species. Honey constituents can be used as signature of geographical identity/product quality. We tested a DNA barcoding approach to characterise 4 honeys. DNA barcoding is a reliable method for honey characterisation and traceability. Abstract: The purpose of this study was to test the ability of DNA barcoding to identify the plant origins of processed honey. Four multifloral honeys produced at different sites in a floristically rich area in the northern Italian Alps were examined by using the rbcL and trnH-psbA plastid regions as barcode markers. An extensive reference database of barcode sequences was generated for the local flora to determine the taxonomic composition of honey. Thirty-nine plant species were identified in the four honey samples, each of which originated from a mix of common plants belonging to Castanea, Quercus, Fagus and several herbaceous taxa. Interestingly, at least one endemic plant was found in all four honey samples, providing a clear signature for the geographic identity of these products. DNA of the toxic plant Atropa belladonna was detected in one sample, illustrating the usefulness of DNA barcoding for evaluating the safety of honey.